The Expression of Testin, Ki-67 and p16 in Cervical Cancer Diagnostics - Aneta Popiel-Kopaczyk; Jedrzej Grzegrzolka; Aleksandra Piotrowska; Mateusz Olbromski; Beata Smolarz; Hanna Romanowicz; Agnieszka Rusak; Monika Mrozowska; Piotr Dziegiel; Marzenna Podhorska-Okolow; Christopher Kobierzycki (Current Issues in Molecular Biology, 2023)
Testin is a protein expressed in normal human tissues, being responsible, with other cytoskeleton proteins, for the proper functioning of cell–cell junction areas and focal adhesion plaques. It takes part in the regulation of actin filament changes during cell spreading and motility. Loss of heterozygosity in the testin-encoding gene results in altered protein expression in many malignancies, as partly described for cervical cancer. The aim of our study was the assessment of the immunohistochemical (IHC) expression of testin in cervical cancer and its analysis in regard to clinical data as well the expression of the Ki-67 antigen and p16 protein. Moreover, testin expression was assessed by Western blot (WB) in commercially available cell lines. The IHC analysis disclosed that the expression of testin inversely correlated with p16 (r = −0.2104, p < 0.0465) and Ki-67 expression (r = −0.2359, p < 0.0278). Moreover, weaker testin expression was observed in cancer cases vs. control ones (p < 0.0113). The WB analysis of testin expression in the cervical cancer cell lines corresponded to the IHC results and showed a weaker expression compared to that in the control cell line. When we compared the expression of testin in cervical cancer cell lines, we found a weaker expression in HPV-negative cell lines. In summary, we found that the intensity of testin expression and the number of positive cells inversely correlated with the expression of Ki-67 (a marker of proliferation) and p16 (a marker of cell cycle dysregulation). This study shows that the combined assessment of testin, Ki-67 and p16 expression may improve cervical cancer diagnostics.